DEVELOPMENT OF INFORMATION SYSTEMS FOR SERVICE AND CUSTOMER COMPLAINTS USING THE EXTREME PROGRAMMING METHOD - Rhaishudin Jafar Rumandan (Jurnal Teknoinfo, 2023)
The Regional Drinking Water Company (abbreviated as PDAM in Indonesian) Tirta Yapono strives to provide the best service for its customers by providing access to information and complaints for the general public. However, currently the provision of information about company programs uses the company's web portal. This is considered insufficient, because the web portal is static or only provides information without interaction with its users. Apart from that, for public complaints, only provide telephone numbers and email complaints. This system causes slow handling of complaints due to the accumulation of incoming complaints via telephone or email. For this reason, a website-based system is needed that can provide services to the community dynamically and the public can submit complaints directly and can communicate with related officers through the website. This study aims to develop a website-based customer service and complaint system using the Extreme Programming (XP) system development method, so that users can interact directly so that information and resolution of complaints can be handled immediately. The XP method is a method for developing an agile development system that is capable of producing a short system and is proven by short development results. The developed customer service and complaint information system can manage new installations, customer complaints, announcements and customer chats. The resulting application is in the good category, because based on usability testing it shows an average value of 90% in the good category, so the application is feasible to use and as needed.